Pengaruh Pendidikan Budi Pekerti Terhadap Karakter Religius Siswa Smpn 2 Tegalsari Banyuwangi - Mar Syahid (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2020)
Abstract The formation ofreligious character is very important to be implemented in the realm of education, especially in schools to change the behavior of students who are not good will be good with akhlakul karimah. Realizing good and noble behavior needs to be held the formation of religious character. The result of the study there is a significant influence between Islamic religious education and manners, tolerance and sincerity of students SMPN from Tegalsari Banyuwangi.